(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Physiology is one of the supporting sciences for the sports training science, which depends on it mainly, as it studies all the details of the player’s physiology responses, and the reactions of body to the training process in terms of external and internal training loads, the authors used the descriptive approach as it is appropriate for the objectives of the research, the aim of this research is to know and compare functional responses and oxygen saturation with blood among futsal and handball players, the research sample was represented by futsal players and handball players in the Faculty of Physical Education and Sports Sciences At Diyala University for the academic year 2023-2024, As for the research problem, it was to identify the reactions associated with performance, as many studies are working to show the good face of the effect of sports practice, while the other side of it is neglected, and what is meant is the negative effect associated with sports practice, which often occurs when the percentage of blood saturation with oxygen decreases after the performance of physical efforts, the authors concluded from the current study a greater effect on the indicators of heart rate (H.R) and diastolic blood pressure rate (Dias.BI.Pr) after (5) minutes From the completion of the effort (recovery) in the handball team than in futsal. There was no effect on the blood oxygen saturation (SPO2) and systolic blood pressure (Sys.BI.PT) after (5) minutes of the completion of the effort (recovery) between the handball and futsal teams. The authors recommend intensifying low-intensity interval load training in developing the heart’s adaptation to physical exertion by increasing the load on the heart and thus bringing about the adaptation process to ensure a return to normal as soon as possible.